1994
DOI: 10.1002/jemt.1070290211
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of small intensely fluorescent (SIF) cells and of sif cell‐associated nerve fibers in the rat superior cervical ganglion

Abstract: Double-labelling immunofluorescence was applied on single sections of the rat superior cervical ganglion to evaluate neurochemistry and connectivity of intraganglionic SIF cells. The synaptic vesicle membrane protein synaptophysin and secretoneurin, a newly discovered neuropeptide derived from secretogranin II, proved reliable molecular markers of this cell type, whereas serotonin and tyrosine hydroxylase immunoreactivities were observed in slightly incongruent SIF cell subpopulations. Immunolabelling for vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…The baskets are mostly related to principal neurons but we have found that some clusters of small cells (presumably SIF cells) are enmeshed in a VIP-IR plexus. A similar relationship of VIP fibers to SIF cells has been described in the rat SCG (Heym et al 1994). The frequency of VIP-IR baskets is modestly elevated by chronic proximal decentralization of the major pelvic ganglion, in contrast to more marked results with TH and NADPH-D.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The baskets are mostly related to principal neurons but we have found that some clusters of small cells (presumably SIF cells) are enmeshed in a VIP-IR plexus. A similar relationship of VIP fibers to SIF cells has been described in the rat SCG (Heym et al 1994). The frequency of VIP-IR baskets is modestly elevated by chronic proximal decentralization of the major pelvic ganglion, in contrast to more marked results with TH and NADPH-D.…”
Section: Discussionmentioning
confidence: 55%
“…Taken together, these data suggest that the emergent fibers are of intraganglionic origin. The likely source would be the large population of NADPH-D principal neurons, since NADPH-D activity has not been noted in SIF cells in the pelvic ganglia (but NADPH-D is present in SIF cells in the rat SCG; Heym et al 1994). The present study confirms the results of Keast (1991) who has established that VIP-IR pericellular baskets are rare in the rat major pelvic ganglion.…”
Section: Discussionmentioning
confidence: 98%
“…Immunoreactivity for TH was found in high concentration in a class of cells with somata which were smaller than, and morphologically distinct from, intracardiac neurons (Fig. Specifically, SIF cells in the heart have been found in previous studies to contain TH in high concentrations (Heym et al, 1994;Mawe et al, 1996). The results of a comparison of morphologic characteristics of the two cell types showed that there was no overlap in somatic dimensions between the smallest neurons and the largest TH-IR cells.…”
Section: Adrenergic Elements In the Atriamentioning
confidence: 56%
“…4D). These were identical in distribution and size to paraganglion cells or SIF cells described previously (Heym et al, 1993(Heym et al, , 1994 and are referred to as SIF cells here after.…”
Section: Calbindin-immunoreactivity In Sympathetic Gangliamentioning
confidence: 98%